Melanotic Tumors of the Nervous System are Characterized by Distinct Mutational, Chromosomal and Epigenomic Profiles. (15th December 2014) - Koelsche, Christian; Hovestadt, Volker; Jones, David T. W.; Capper, David; Sturm, Dominik; Sahm, Felix; Schrimpf, Daniel; Adeberg, Sebastian; Böhmer, Katja; Hagenlocher, Christian; Mechtersheimer, Gunhild; Kohlhof, Patricia; et al.
Abstract Melanotic tumors of the nervous system show overlapping histological characteristics but differ substantially in their biological behavior. In order to achieve a better delineation of such tumors, we performed an in‐depth molecular characterization. Eighteen melanocytomas, 12 melanomas, and 14 melanotic and 14 conventional schwannomas (control group) were investigated for methylome patterns (450k array), gene mutations associated with melanotic tumors and copy number variants (CNVs). The methylome fingerprints assigned tumors to entity‐specific groups. Methylation groups also showed a substantial overlap with histology‐based diagnosis suggesting that they represent true biological entities. On the molecular level, melanotic schwannomas were characterized by a complex karyotype with recurrent monosomy of chromosome 22q and variable whole chromosomal gains and recurrent losses commonly involving chromosomes 1, 17p and 21. Melanocytomas carried GNAQ/11 mutations and presented with CNV involving chromosomes 3 and 6. Melanomas were frequently mutated in the TERT promoter, harbored additional oncogene mutations and showed recurrent chromosomal losses involving chromosomes 9, 10 and 6q, as well as gains of 22q. Together, melanotic nervous system tumors have several distinct mutational and chromosomal alterations and can reliably be distinguished by methylome profiling.